Peningkatan Aktivitas dan Hasil Belajar Proyeksi Ortogonal Melalui Model Problem Based Learning Berbantuan 3D Printing: Improving Students’ Activity and Learning Outcomes in Orthogonal Projection Through 3D Printing-Assisted Problem-Based Learning - Mohammad Dani Subarna; Yusep Sukrawan; Ramdhani (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This research was motivated by the students' lack of active participation and low cognitive learning outcomes in understanding Orthogonal Projection concepts. The root of the problem stemmed from the dominance of conventional instructional strategies that neglected the use of physical visual aids. Therefore, this study was conducted to determine the effectiveness of implementing Problem-Based Learning (PBL) integrated with 3D Printing technology in improving students' active participation and learning outcomes. The research applied a Classroom Action Research (CAR) approach adapting the Kemmis and McTaggart model, executed in two cycles. The participants included 40 students of class X TO 2 at SMKN 1 Kota Sukabumi. Data were analyzed using quantitative descriptive techniques, percentage calculations, and the Normalized Gain (N-Gain) metric. The findings demonstrated consistent positive progress. Classical student learning participation gradually increased from 64% (Poor category) in the pre-cycle to 89% (Active category) in Cycle I, and reached 93.16% (Very Active category) at the end of the intervention in Cycle II. This success was accompanied by an increase in cognitive achievement, where the classical completeness rate successfully reached 58% in Cycle I from an initial 13%, and culminated at 85% (Good category) in the second cycle. The N-Gain analysis confirmed the effectiveness of the intervention with a score of 0.74, categorized as high. In conclusion, the application of the 3D Printing-assisted PBL model significantly resolved students' passivity in the classroom and improved their learning outcomes in Orthogonal Projection materials.